Preliminary post findings in BPPV patients presenting with normal vestibulo-ocular reflex (VOR) gain and observable saccades using video head impulse test (vHIT) - Omar, Amira; Jamaluddin, Saiful Adli; Al- Hadeethi, Yahia F. Hussein (2019)
Introduction: Benign Paroxysmal Positional Vertigo (BPPV) is a common peripheral hypofunction reported in dizzy clinics and is mostly dependant on positional manoeuvres for diagnosis and intervention. Although video head impulse test (vHIT) is not warranted in BPPV cases however due to the subjectivity of patients’ reports, it is sometimes performed on patients to exclude potential vestibular ocular reflex (VOR) deficits. Objective: Observe differentiation patterns of VOR gain and possible corrective eye movements in patients with BPPV using vHIT. Method: Two male and five female participants with BPPV were tested using vHIT. Three patients out of the seven who were relieved from post Canalith Repositioning Procedure (CRP) were tested again with vHIT. Ten responses for each semicircular canal stimulation were recorded for every participant by making small unpredictable head movements. Results: VOR gain for all canal stimulations were found to be within the normal range. All participants showed consistent pre-treatment corrective saccadic eye movements with gain between 0.12 to 1.35 and latency of onset between 80 to 220 milliseconds after vHIT was initiated. All saccades were recorded in lateral canals only despite patients presenting with anterior or posterior canal BPPV. Post-treatment vHIT findings showed that the saccades have diminished for two participants while a participant showed reduced saccades. Conclusions: Rapid head thrusts could trigger VOR adjustments in patients with dislodged otoconia such in BPPV cases. Further investigation is necessary to validate the potential use of vHIT as a tool to supplement findings via manoeuvres especially to check the effectiveness of CRP.